Student attrition in gender-atypical fields of study: a case of disapproval by parents and friends or lacking social integration? - Jusri, Regina (Zeitschrift für Erziehungswissenschaft, 2025)
In most industrialized countries, the choice of college majors is segregated by gender. Few students enroll in gender-atypical majors. Previous studies suggested that some attrition risks are associated with the gender composition of majors. In this paper, I investigated whether students in gender-atypical majors are more likely to leave the major by dropping out or switching to a different major with more same-sex students than those majoring in gender-typical subjects. Furthermore, I hypothesized that the relation between gender composition and non-completion risks is partially mediated by two social processes, namely poor social integration and disapproval of the major from parents and friends. Using data from undergraduate students from the German National Educational Panel Study, I conducted discrete-time survival analyses and a KHB decomposition. I found that both men and women in gender-atypical majors have a higher risk of switching to a major with a higher percentage of same-sex students than students in gender-typical majors. Women in gender-atypical majors also have a higher dropout risk. Poor social integration and disapproval of the major by parents and friends increase the switching risk and, in the case of social integration, also the dropout risk for all students. However, these two aspects cannot explain the higher attrition risk for students in gender-atypical majors, with one exception. Only for women in gender-atypical majors, lower approval of the major by friends partly mediates the association between the gender composition of the major and the risk of switching to a more female-dominated major.